Peripheral Blood NMLR Can Predict 5-Year All-Cause Mortality in Patients with Chronic Obstructive Pulmonary Disease - Li Y; Ge S; Liu J; Li R; Zhang R; Wang J; Pan J; Zhang Q; Zhang J; Zhang M (International Journal of COPD)
Yuer Li,1 Shaobo Ge,1 Jin Liu,1 Rui Li,1 Rui Zhang,1 Juan Wang,2 Jianli Pan,3 Qiuhong Zhang,1 Jie Zhang,1 Ming Zhang1 1Department of Respiratory and Critical Care Medicine, the Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Department of Ultrasound, the Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 3Department of Special Need, Xi’an Children’s Hospital, Xi’an, Shaanxi, People’s Republic of ChinaCorrespondence: Ming Zhang, Department of Respiratory and Critical Care Medicine, the Second Affiliated Hospital of Xi’an Jiaotong University, No. 157 West Fifth Road, Xi’an, Shaanxi, 710004, People’s Republic of China, Email zhangmingdr@163.comBackground: Chronic obstructive pulmonary disease (COPD) is characterized by pulmonary and systemic inflammation. The peripheral blood (neutrophil + monocyte)/lymphocyte ratio (NMLR) can predict the clinical outcomes of several inflammatory diseases. However, its prognostic value in COPD remains unknown.Methods: This retrospective study included 870 patients with COPD due to acute exacerbation, and the 5-year all-cause mortality of these patients was recorded. The Kaplan-Meier method was used to compare the mortality risk of these patients according to their NMLR value. Multivariable COX hazard regression and restricted cubic spline model were used to assess the relationship between the NMLR and 5-year all-cause mortality of patients with COPD.Results: The NMLR values of non-surviving patients with COPD were significantly increased compared to the survivors [3.88 (2.53– 7.17) vs 2.95 (2.08– 4.89), P=0.000]. The area under the NMLR receiver operating characteristic curve for predicting the 5-year all-cause mortality of COPD patients was 0.63. Kaplan-Meier survival curves showed that the 5-year all-cause mortality of COPD patients was significantly increased when the admission peripheral blood NMLR was ≥ 5.90 (27.3% vs 12.4%, P=0.000). The COX regression model showed that NMLR was an independent predictor of 5-year all-cause mortality in COPD patients (hazard ratio=1.84, 95% confidence interval: 1.28– 2.64, P=0.001). Moreover, the restricted cubic spline model showed a non-linear relationship between NMLR and COPD death risk (Pnon-linear < 0.05).Conclusion: The admission peripheral blood NMLR is a significant predictor of 5-year all-cause mortality in patients with COPD, and high NMLR values may indicate a poor clinical prognosis.Keywords: chronic obstructive pulmonary disease, neutrophil, monocyte, lymphocyte, inflammation, prognosis